TGF-? Family Signaling in Drosophila. - Upadhyay, A.; Moss-Taylor, L.; Kim, M.J.; Ghosh, A.C.; O'Connor, M.B. (Cold Spring Harbor perspectives in biology, 2017)
The transforming growth factor ? (TGF-?) family signaling pathway is conserved and ubiquitous in animals. In Drosophila, fewer representatives of each signaling component are present compared with vertebrates, simplifying mechanistic study of the pathway. Although there are fewer family members, the TGF-? family pathway still regulates multiple and diverse functions in Drosophila. In this review, we focus our attention on several of the classic and best-studied functions for TGF-? family signaling in regulating Drosophila developmental processes such as embryonic and imaginal disc patterning, but we also describe several recently discovered roles in regulating hormonal, physiological, neuronal, innate immunity, and tissue homeostatic processes.